The Effects of Listening to Persian Music on the Hand Dexterity and Depression in a Patient with Stroke: A Case Report - Reyhaneh Maktoufi; Nastaran Ghotbi; Noureddin Nakhostin Ansari (Shiraz University of Medical Sciences, 2015)
Introduction: Nowadays the use of music therapy for neurological disorders in developed countries is widely emphasized. Despite this, there is little scientific evidence regarding the use of this method for the treatment of Iranian patients with stroke. Case report: Since Iranian patients are more familiar with Persian music, this study was performed to describe the effects of listening to the Persian music played with Daf (an Iranian music instrument) in a 54-year-old man with chronic stroke. Discussion: This case report could show for the first time, the positive effect of passive listening to Persian music with Iranian Daf instrument on the hand dexterity and depression in a patient with chronic stroke.